Pengaruh Literasi Keuangan, Kualitas Layanan E-commerce dan Gaya Hidup terhadap Perilaku Keuangan Mahasiswa dalam Berbelanja Online - Anisa Nurmelinda; Teti Safitri (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
Technological developments in Indonesia have progressed rapidly, marked by the emergence of smart technologies that integrate various dimensions of human life. This transformation has changed the function of the internet, which was originally only a means of communication, into a broader platform, including access to social media and the formation of Indonesian society's shopping behavior patterns. This evolution has enabled the internet to be used as a medium for electronic commerce transactions. This study uses a quantitative correlation method. A quantitative correlation approach is a type of research that uses data collection to determine the level of relationship between variables. The purpose of this study is to characterize and examine how independent variables such as lifestyle determinants, financial literacy, and e-commerce quality influence the dependent variable, or financial behavior. The results of the study show that of all the independent variables tested based on the hypothesis, the variables of financial literacy and e-commerce service quality have a positive influence, while the lifestyle variable has a negative influence on financial behavior. The variables of financial literacy and e-commerce service quality show high values and greatly contribute to the influence of financial behavior variables. This is because the higher the financial literacy of students, the greater the influence on financial behavior in their environment.